Implementation of Dynamic Fuzzy Logic Control of Traffic Light with Accident Detection and Action System using iTraffic Simulation - Abdulrahman Abdullah Alkandari; Imad Fakhri Al-Shaikhli (Institute of Advanced Engineering and Science, 2018)
Traffic is one of the most common issues in the big cities around the world. Thus, develop and improve the traffic light control systems became the focus of recent studies. To solve the problem, we proposed a dynamic hybrid fuzzy logic control system that is further branched into two separate systems: An Accident Detection system and an Action system that is intended to solve the congestion related to the vehicular traffic. The primary target of this paper is to discuss the Action system, which depends on the Accident Detection system. This paper explained the two parts of the Action system. It showed the improvement of the Action system with %9.32 in total car crossed. It also presented different scenarios using iTraffic simulation and description of each scenario is displayed with details about the road variables and the simulation results with and without the action system.